THE INFLUENCE OF EDUCATION LEVEL AND TRAINING ON THE PERFORMANCE OF TEACHERS OF PUBLIC HIGH SCHOOL 2 SIDRAP - Fadel Muhammad; Gazali Amin; Dian Nirmasari (Jurnal Mahasiswa Manajemen, 2025)
This study aims to determine and analyze whether there is an influence of education level and training on the performance of teachers at State Senior High School 2 Sidrap. The data used in this study are primary data and secondary data, data collection using primary data is by filling out questionnaires distributed to all teachers at State Senior High School 2 Sidrap who are samples. The population in this study which is also a sample is all educators/teachers at State Senior High School 2 Sidrap totaling 60 people including the principal, and the determination of the number of samples using quota sampling techniques. This study is an associative study and hypothesis testing using multiple linear regression analysis, t-test and F-test. The results of this study indicate that education level and training simultaneously have an influence on the performance of teachers at State Senior High School 2 Sidrap. While the partial test shows that the education level variable partially has no influence on the performance of teachers at State Senior High School 2 Sidrap, while the training variable partially has an influence on the performance of teachers at State Senior High School 2 Sidrap.